# FIND THE VALUE OF x : 2-2x - 3/2x + 3 = 3x +4/x+2`` ANSWER= -1`-:2` ``

### 1 Answer | Add Yours

Assuming the given equation is `2-(2x-3)/(2x+3)=(3x+4)/(x+2)`

Then, `(4x+6-2x+3)/(2x+3)=(3x+4)/(x+2)`

`rArr (2x+9)/(2x+3)=(3x+4)/(x+2)`

cross multiplying we get,

`(2x+9)(x+2)=(3x+4)/(2x+3)`

`rArr 2x^2+13x+18=6x^2+17x+12`

`rArr 4x^2+4x-6=0`

Dividing both sides by 2,

`2x^2+2x-3=0`

This is a quadratic equation, having general solution as,

`x= (-2+-sqrt(2^2-4*2*(-3)))/(2*2)`

`=(-1+-sqrt7)/2 `

=> answer.